Upaya Peningkatan Literasi melalui Media Majalah Dinding (Mading) Berbasis Kearifan Lokal oleh Mahasiswa Kampus Mengajar di SDN Tambakromo 1 - Aviani, Ranita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
One of the fundamental problems in Indonesia is the low level of community literacy. In order to improve literacy in Indonesia, the government has created the National Literacy Movement program, which consists of the School Literacy Movement (GLS), Family Literacy Movement, and Community Literacy Movement. In support of these activities, the Ministry of Education and Culture has launched a new policy, namely the Independent Learning Free Campus, one of which is the Campus Teaching program which focuses on improving literacy and numeracy in schools. One of the efforts made by Campus Teaching students to improve school literacy at SDN Tambakromo 1 is by creating a bulletin board with a local wisdom theme. The method used in this research is a descriptive qualitative method, where data collection techniques are through observation and interviews. The research results show an increase in literacy among students at SDN Tambakromo 1 through the local wisdom-themed bulletin board. This is due to the students' interest in the local culture or wisdom that is used in the bulletin board with their own creativity. In addition to increasing student literacy, creating bulletin boards also increases the creativity and skills of students at SDN Tambakromo 1.